OPTIMALISASI PERMAINAN ULAR TANGGA DALAM MENINGKATKAN KONSENTRASI SISWA MI AZ ZAINIYAH II KARANGANYAR - Maulidah, Hamidatul; Feriska Listrianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the application of the snakes and ladders game method as a tool to increase student concentration at MI Az Zainiyah II KarangAnyar. The snakes and ladders game has been modified by adding educational elements to integrate learning aspects with play activities. The main aim of this research is to observe the impact of using the snakes and ladders game on student engagement and concentration during the learning process. The results showed that students demonstrated significant improvements in concentration and engagement when engaged in games that combined elements of learning with entertainment. Evaluations were carried out through direct observation and discussions with students, revealing that students were more focused and motivated in completing the learning tasks encountered during the game. Although some challenges, such as maintaining motivation and adjusting the level of difficulty, were encountered during implementation, the benefits of this method show that a creative approach to learning can create a more interactive and enjoyable learning environment. This research concludes that an optimized snakes and ladders game can be an effective educational tool, offering the potential to improve the quality of learning and student concentration in the classroom.